PERTANGGUNGJAWABAN PIDANA KURATOR YANG MELAKUKAN PENGGELAPAN DALAM PENGURUSAN DAN PEMBERESAN HARTA PAILIT - Rianto; Hendri Jayadi; Paltiada Saragi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Bankruptcy is a general confiscation of all assets of a bankrupt debtor whose management and settlement is carried out by the curator under the supervision of a supervisory judge, (Article 1 paragraph 1 of Law No. 37 of 2004) Bankruptcy regulations are made and issued because the assets of the debtor are not sufficient to be distributed to creditors as a result of the seizure of bankruptcy assets. With the aim that to protect creditors from obtaining their rights in bankruptcy, to provide opportunities for debtors and creditors to negotiate and make mutual agreements or even provide protection to creditors and debtors for errors or omissions from the curator in the bankruptcy estate. The purpose and objective of writing this thesis is to find out the responsibilities of a curator who made mistakes or omissions in the management and settlement of bankrupt assets and also to find out the extent of legal protection for debtors and creditors against actions taken by the curator. The research method used is a normative juridical research with a statutory approach and uses a decision study where the author analyzes the position of debtors and or creditors who file a bankruptcy application and have legal standing as an applicant for bankruptcy to companies, both private and state-owned companies.